Electroacupuncture Inhibits Visceral Nociception via Somatovisceral Interaction at Subnucleus Reticularis Dorsalis Neurons in the Rat Medulla - Yu, Lingling; Li, Liang; Qin, Qingguang; Yu, Yutian; Cui, Xiang; Rong, Peijing; Zhu, Bing (Frontiers in Neuroscience, 2018)
Electroacupuncture (EA) is an efficacious treatment for alleviating visceral pain, but the underlining mechanisms are not fully understood. This study investigated the role of medullary subnucleus reticularis dorsalis (SRD) neurons in the effects of EA on visceral pain. We recorded the discharges of SRD neurons extracellularly by glass micropipettes on anaesthetized rats. The responses characteristics of SRD neurons to different intensities of EA (0.5, 1, 2, 4, 6 and 8 mA, 0.5 ms, 2 Hz) on acupoints “Zusanli” (ST 36) and “Shangjuxu” (ST 37) before and during noxious colorectal distension (CRD) were analyzed. Our results indicated that SRD neurons responded to either a noxious EA stimulation ranging from 2 - 8 mA or to noxious CRD at 30 and 60 mmHg by increasing their discharge frequency at an intensity-dependent manner. However, during the stimulation of both CRD and EA, the increasing discharges of SRD neurons induced by CRD were significantly inhibited by 2 - 8 mA of EA. Furthermore, SRD neurons can encode the strength of EA, where a positive correlation between current intensity and the magnitude of neuronal responses to EA was observed within 2 - 6 mA. Yet, the responses of SRD neurons to EA stimulation reached a plateau when EA exceeded 6 mA. In addition, 0.5 - 1 mA of EA had no effect on CRD-induced nociceptive responses of SRD neurons. In conclusion, EA produced an inhibiting effect on visceral nociception in an intensity-dependent manner, which probably is due to the somatovisceral interaction at SRD neurons.